The Inspection of Education: a decalogue of pending challenges to be met - Gómez Pimpollo Morales, Nohemi (Avances en Supervisión Educativa, 2024)
This article presents some of the challenges facing education inspection at the present time. It starts from the unusual certainty that the inspection model is basically defined on a national basis, despite the emphasis that is often placed on the differences that are generated in the different Autonomous Communities. It raises the debate around a total of ten challenges for the improvement of the inspection function, grouped into three axes depending on whether they have to do with ethics, professional performance or are shared with other professional groups because they are related to the socio-economic environment. Some hints are given on other issues that may merit the same consideration and could be the subject of future debates.